Optimizing African Port Hinterland Connectivity Using Markov Processes, Max-Flow, and Traffic Flow Models: A Case Study of Dar es Salaam Port - (:unkn) unknown (MDPI AG, 2025)
Dar es Salaam Port, a crucial logistical hub in East Africa, faces significant challenges related to cargo handling efficiency, road congestion, and capacity constraints. The port’s performance is pivotal for regional trade, necessitating a comprehensive analysis to identify and address operational inefficiencies. This study employed Markov processes to evaluate cargo handling and delivery times, cellular automata for simulating road traffic dynamics, and max-flow models to optimize cargo flow from the port to hinterland destinations. The analysis incorporated factors such as road and rail capacities, traffic conditions, and environmental impacts. The Markov process model indicated that cargo spends 15% of its time waiting at the port, 50% in transit, and 10% delayed, with only 25% successfully delivered. The Cellular Automata simulation revealed severe congestion for heavy trucks due to poor road conditions, with an additional 10 min delay during the rainy season. The max-flow model highlighted that while the road and rail networks generally meet demand, significant bottlenecks exist, particularly for Lubumbashi, which faces a capacity shortfall of 500 t/day. The findings offer actionable insights for stakeholders. Logistics operators can leverage the framework to predict delays, optimize resource allocation, and improve delivery reliability. Policymakers can prioritize strategic investments in infrastructure upgrades, traffic management, and road maintenance to reduce delays and congestion. Scholars can adopt the integrated methodology to analyze similar systems. Together, these efforts can enhance Dar es Salaam Port’s operational efficiency, reduce transit times, and support regional trade development..